Economic Development and Peacebuilding in the USA: Lesson For Nigeria - Ayeni, Evans Oluwagbamila; Abdullahi, Nuruddeen Abba (University of Nigeria Journal of Political Economy, 2024)
The objective of achieving economic development is because of its capacity to improve living conditions and address the challenges of unemployment and poverty that have been the root cause of violent conflict. The inability of many developing countries to follow the process of economic development that addresses unemployment and poverty is the rationale for this study. The objective of this study is to analyse the role of economic development in peacebuilding in the USA, with the view to drawing lessons for Nigeria. The research method adopted for this paper is, the documentary method. The finding of this study is that the presence of strong institutions that promote access to education and technology advancement to create equal opportunity for everybody to succeed is the magic wand in achieving economic development in the U.S, while the absence of strong institutions in Nigeria produce strong leaders that war against education and technological advancement to create unfavourable environment for people to succeed. The study recommends that the civil society organisation should persuade the general public and the ruling elite to build strong institutions that will promote access to education, technological advancement and create equal opportunity for everybody to succeed in respective of individuals’ background. The suggested solution will produce an educated population to favour the voice of citizens for government effectiveness, innovative and creative minds that will effectively allocate resources into productive investment for economic development in Nigeria.